Letter to the Editor in response to "Our unrequited love for natural ingredients, " by Burdock and Wang. (January 2018) - Harman, Christie L.; Taylor, Sean V.
Abstract: This letter is in response to the review article "Our unrequited love for natural ingredients" authored by Burdock and Wang in the September edition of FCT. Our purpose is to clarify the procedure used by the FEMA Expert Panel for the safety evaluation of natural flavor complexes, as well as to note and/or correct inaccuracies that we have identified within the article.